Electrical cream separator coupled with vacuum filtration for the purification of eimerian oocysts and trichostronglyid eggs - El-Ashram, Saeed (Sci Rep, 2017)
Several methods have been proposed for separation of eimerian oocysts and trichostronglyid eggs from extraneous debris; however, these methods have been considered to be still inconvenient in terms of time and wide-ranging applications. We describe herein an alternative way using the combination of electrical cream separator and vacuum filtration for harvesting and purifying eimerian oocysts and haemonchine eggs on large-scale applications with approximately 81% and 92% recovery rates for oocysts and nematode eggs obtained from avian and ovine faeces, correspondingly. The sporulation percentages as a measure of viability in the harvested oocysts and eggs from dry faecal materials are nearly 68% and 74%, respectively, and 12 liters of faecal suspension can be processed in approximately 7.5 min. The mode of separation in terms of costs (i.e. simple laboratory equipments and comparably cheap reagents) and benefits renders the reported procedure an appropriate pursuit to harvest and purify parasite oocysts and eggs on a large scale in the shortest duration from diverse volumes of environmental samples compared to the modified traditional sucrose gradient, which can be employed on a small scale.